Quantitative results of an immunohistochemical study of metalloproteinase-2 in trophoblast at TORCH infection on abortion material in the gestation period 7-8 weeks. - A. V. Hoshovska; I. S. Davydenko; V. M. Hoshovskyi; O. M. Davydenko; S. M. Yasnikovska (Морфологія, 2020)
Background. This study is a fragment of a series of immunohistochemical studies of trophoblast with TORCH infection, which are scheduled to be carried out at different gestational dates. This article is devoted to the results of studies of trophoblast during gestation of 7-8 weeks. Objective. Using the immunohistochemical method, to establish the features of the expression of metalloproteinase-2 in various types of trophoblast with TORCH infection compared with observations without an infectious process. Methods. The study examined abortion material 7-8 weeks of gestation. The main group of the study consisted of 18 observations of TORCH infection, and the control group - 17 observations of an aborted pregnancy without signs of an infectious process (abortion for social reasons). An immunohistochemical procedure was performed on metalloproteinase-2 with primary antibodies and a polymer antigen imaging system using DAKO diaminobenzidine. The method of microdensitometry in a specialized computer program ImageJ evaluated the optical density of the color. Results. According to the results of immunohistochemical studies using computer microdensitometry at a gestational age of 7-8 weeks, both with TORCH infection and without an infectious process, the very high expression of metalloproteinase-2 is observed in the invasive trophoblast, the smallest - in the syncytotrophoblast of the choric villi, and intermediate values are noted in chorionic villus cytotrophoblast and cell column cytotrophoblast. With TORCH infection, the expression of metalloproteinase-2 is reduced in all types of trophoblast (cytotrophoblast of chorionic villi, cytotrophoblast of cell columns, invasive cytotrophoblast in endometrial fragments), except for syncytotrophoblast of chorionic villi. Conclusion. According to the results of immunohistochemical studies, using computer microdensitometry at a gestational age of 7-8 weeks, both with TORCH infection and without an infectious process, the largest expression of metalloproteinase-2 is observed in invasive trophoblast, the smallest - in the syncytiotrophoblast of chorionic villi, and intermediate indices are noted in the cytotrophoblast of chorionic villi and the cytotrophoblast of cell columns. With TORCH infection, the expression of metalloproteinase-2 decreases in all types of trophoblast, excluding the syncytiotrophoblast of chorionic villi.